Coupled Polymer-Membrane Equilibration and Cavity Ring-down Spectrometry for the Highly Sensitive Determination of Dissolved Methane in Environmental Waters. (11th February 2021) - Munksgaard, Niels C.; Nelson, Paul N.
Abstract: High sensitivity field-based analysis of dissolved methane in surface water and groundwater is needed to monitor the environmental impacts of natural gas-field development and understand microbial carbon cycling in water bodies. A new analytical technique using a polymer membrane contactor coupled to a laser-based cavity ring-down spectrometer was developed and tested. By recirculating a water sample for approximately 10 mins, equilibrium was established between dissolved methane in the sample and methane in the measured gas phase according to Henry's Law. The performance of the system was investigated by replicate analyses of several different water samples, spike recovery tests, comparison to analysis by head-space gas chromatography, and consideration of memory effects. The technique provided an adequate detection limit for the determination of natural background concentrations of methane in environmental waters and was approximately 28 times more sensitive than analysis by gas chromatography. The system is field-capable, simple to operate and calibrate, and takes advantage of the low-drift characteristics of the cavity ring-down spectrometer.